2018
DOI: 10.1212/wnl.0000000000005031
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenicity of antiepileptic dual therapy

Abstract: Our data indicate that the excess risk of dual therapy over monotherapy is contributed largely by topiramate or valproate. The complex pharmacokinetic and pharmacodynamic effects of dual therapy adversely influence MCM risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 7 publications
0
19
0
7
Order By: Relevance
“…The Kerala study 66 has identified a signal of increased MCM risk after in utero exposure to clobazam, based on two MCM cases from nine pregnancies (MCM rate of 22.2%, 95% CI: 6.3–54.7). A subsequent study 67 from Kerala reported 12 MCMs from 125 polytherapy clobazam exposures (MCM rate of 9.6%), and 3 MCMs from 38 clonazepam polytherapy exposures (MCM rate of 7.9%). A French healthcare database cohort study 68 of 1,886,825 pregnancies identified a signal for microcephaly among 980 exposures to clonazepam.…”
Section: Monotherapymentioning
confidence: 99%
“…The Kerala study 66 has identified a signal of increased MCM risk after in utero exposure to clobazam, based on two MCM cases from nine pregnancies (MCM rate of 22.2%, 95% CI: 6.3–54.7). A subsequent study 67 from Kerala reported 12 MCMs from 125 polytherapy clobazam exposures (MCM rate of 9.6%), and 3 MCMs from 38 clonazepam polytherapy exposures (MCM rate of 7.9%). A French healthcare database cohort study 68 of 1,886,825 pregnancies identified a signal for microcephaly among 980 exposures to clonazepam.…”
Section: Monotherapymentioning
confidence: 99%
“…86 As a matter of fact, combination of sodium of valproate or topiramate is an independent risk factor of major congenital malformations. 87 Lastly, patients' comorbidities must carefully be screened. Without going into an exhaustive list, some frequent examples can be highlighted.…”
Section: Choosing Asd Upon Their Safety Profile?mentioning
confidence: 99%
“… 86 As a matter of fact, combination of sodium of valproate or topiramate is an independent risk factor of major congenital malformations. 87 …”
Section: Pharmacological Managementmentioning
confidence: 99%
“…The Kerala (India) Registry of Epilepsy and Pregnancy, established in 1998, published its findings of 1021 monotherapy and 368 dual AED exposures in pregnancy through 2013. 9 The AEDs used most commonly were carbamazepine, valproate, phenobarbital, and clobazam. The MCMs occurred in 70 (6.8%) of monotherapy and 44 (11%) of dual therapy exposed pregnancies.…”
Section: Commentarymentioning
confidence: 99%